Effectiveness and cost of treatment with maraviroc in HIV infection - Sacchi, Viola; Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2009)
Since 1995, life expectancy and quality of life of HIV patients improved significantly due to the use of Highly Active Anti-Retroviral Therapy (HAART), consisting of different combinations of three classes of antiretroviral agents, nucleoside and non-nucleoside reverse transcriptase inhibitors, and protease inhibitors. Recently, new treatment options for individuals developing resistance to these drugs have become available, with the appearance of new drug classes like integrase inhibitors, fusion inhibitors and CCR5 antagonists. Maraviroc is the first antiretroviral agent belonging to the latter drug class approved for clinical use. CCR5 receptor antagonists act by blocking the interaction of the HIV virus with the CCR5 chemokine receptor, a co-receptor essential to the entry process of R5-tropic viruses. The drug is indicated, in combination with other antiretroviral products, for treatment-experienced adult patients infected with only CCR5-tropic HIV-1 detectable virus strains. Results of main phase III clinical trials indicate that maraviroc, in combination with optimized background therapy (OBT), causes significantly greater reductions in viral load and increases in CD4+ cell count, as compared to OBT alone in this kind of patients. In Italy, the monthly cost of maraviroc therapy is about € 780. A number of economic evaluations, performed for different settings, demonstrate that the therapy including maraviroc is cost-effective if compared to OBT alone, determining an ICER generally below the threshold of three times the GDP per capita. In the Italian context, the ICER determined by OBT + maraviroc vs OBT alone is approximately 45,000 €/LYG.